Integrated Marketing Communication Effecting Decision Making The Consumer’s to One Tampon One Product in Municipality Kanchanaburi Province. - Kitiyanan, Sanchai; Sriboonnak, Suthipot; Kanprom , Supattra; Khamlek, Manit (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed to integrated marketing communication effecting decision making the consumer’s to one tampon one product in municipality Kanchanaburi province. To compare the decision to use the consumer’s to purchase one tampon one product in municipality Kanchanaburi province classified by personal factors. And to study the integrated marketing communication factors that affect the decision to use the consumer’s to purchase one tampon one product in municipality Kanchanaburi province. The sample included 400 users in general users with one tampon one product in municipality Kanchanaburi province, selected by Accidental sampling. The instrument was a 5-level rating scale questionnaire with content validity 0.67-1.00 and reliability 0.90 to collect data which were analyzed in tetms of percentage, mean, standard deviation And analysis of t One-way analysis of variance And analysis of multiple correlation coefficients Determine the level of statistical significance at 0.05 The findings: 1. Integrated marketing communication effecting decision making the consumer’s to one tampon one product in municipality Kanchanaburi province as follows 1.1 Integrated marketing communication effecting decision making the consumer’s to one tampon one product in municipality Kanchanaburi province the study indicated that Overall, the level of opinion is at a high level. And when considering each aspect, it is at a high level in all aspects The respondents gave the highest average score, direct sales using employees, followed by advertising, sales promotion, direct marketing and and news and public relations 1.2 The decision to use the consumer’s to purchase one tampon one product in municipality Kanchanaburi province in the overall picture, found that it was at a high level. And when considering each aspect, it is at a high level in all aspects respondents gave priority to post-purchase behavior, purchasing decisions, needs, the evaluation of alternatives and seeking Needs In the evaluation of options. 2. Decision to use the consumer’s to purchase one tampon one product in municipality Kanchanaburi province classified by personal factors, it was found that gender, age, education level, and income were different. The decision to use the consumer’s to purchase is no different. While different incomes have different levels of decisions, with Income not more than 20,000 baht, average more than income 40,001- 60,000 baht and different careers have different levels of decisions by State enterprise employees / civil service There are more levels of decision making to buy OTOP products than employees of private companies. 3. Integrated marketing communication in advertising (x1) in direct sales using staff (x2) direct marketing (x5) that affect the decision to use the consumer’s to purchase one tampon one product (y) There is a coefficient of prediction that is able to predict the decision to use the consumer’s to purchase one tampon one product in municipality Kanchanaburi province by 17 percent and can create the regression equation as follows. y = 3.25 + 0.05x1 + 0.04x2 + 0.07x5 And forecasting equations in the form of standard points as follows. Zy = 0.10x1 + 0.11x2 + 0.13x5 Article history: Received 19 November 2019 Revised 9 January 2020 Accepted 11 January 2020 SIMILARITY INDEX = 0.00 %